2021
DOI: 10.1029/2020gl091564
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron Precipitation Observed by FIREBIRD‐II Potentially Driven by EMIC Waves: Location, Extent, and Energy Range From a Multievent Analysis

Abstract: We evaluate the location, extent, and energy range of electron precipitation driven by ElectroMagnetic Ion Cyclotron (EMIC) waves using coordinated multisatellite observations from near‐equatorial and Low‐Earth‐Orbit (LEO) missions. Electron precipitation was analyzed using the Focused Investigations of Relativistic Electron Burst Intensity, Range and Dynamics (FIREBIRD‐II) CubeSats, in conjunction either with typical EMIC‐driven precipitation signatures observed by Polar Orbiting Environmental Satellites (POE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 84 publications
8
46
0
Order By: Relevance
“…Figures 2d and 2e are relative to the wave-driven REP events only, for which we can estimate an L-shell extent (ΔL), as defined in Figure 1a. From the scatter plot of ΔL versus MLT (Figure 2d), events identified in the pre-midnight sector tend to be wider than those identified in the post-midnight sector, though the majority of the events have extents of <0.3 L. This could be the result of different wave or plasma background properties across midnight which in turn determine spatial differences where conditions for pitch-angle scattering are more favorable [as suggested in Capannolo et al (2021)]. Although the choice of the ΔL definition is not unique and could affect the minimum/maximum extent [as also mentioned in Supporting Information S1 and Gasque et al ( 2021)],…”
Section: Distribution and Intensity Of Rep Near Midnightmentioning
confidence: 95%
See 1 more Smart Citation
“…Figures 2d and 2e are relative to the wave-driven REP events only, for which we can estimate an L-shell extent (ΔL), as defined in Figure 1a. From the scatter plot of ΔL versus MLT (Figure 2d), events identified in the pre-midnight sector tend to be wider than those identified in the post-midnight sector, though the majority of the events have extents of <0.3 L. This could be the result of different wave or plasma background properties across midnight which in turn determine spatial differences where conditions for pitch-angle scattering are more favorable [as suggested in Capannolo et al (2021)]. Although the choice of the ΔL definition is not unique and could affect the minimum/maximum extent [as also mentioned in Supporting Information S1 and Gasque et al ( 2021)],…”
Section: Distribution and Intensity Of Rep Near Midnightmentioning
confidence: 95%
“…A recent study using high-resolution POES data by Gasque et al (2021) indeed clarifies that the midnight REP events with wider spatial extent (ΔL ∼1-2.5) reported by Shekhar et al (2017) based on 16 s resolution POES data also exhibit localized scales. Additionally, some works studied the association of REP with proton precipitation as a proxy for electromagnetic ion cyclotron (EMIC) wave activity, or with in situ or ground-based EMIC waves (e.g., Capannolo et al, 2021;Carson et al, 2012;Hendry et al, 2016). EMIC-driven precipitation seems to occur predominantly near dusk, although Carson et al (2012) showed that it could also extend until ∼3 MLT, with a peak in occurrence at midnight.…”
mentioning
confidence: 99%
“…Also, the peak electron flux at >30 keV with very low fluxes of >100 keV implies that most detections were lower-energy electrons with less than 100 keV or they were possibly contaminated by 200-2,700 keV protons (Evans & Greer, 2004). Since EMIC waves are known to interact typically with relativistic electrons with energies higher than a few hundred keV (e.g., Capannolo et al, 2021;Hendry et al, 2017;Miyoshi et al, 2008), we checked relativistic electron precipitation from the >6,900 keV proton channel (P6), which also responded to >700 keV electrons (E4 channel), but no relativistic electrons were detected during this event (Figure S3c). According to Fu et al (2018), EMIC waves can also interact with <100 keV electrons when the ambient plasma density and frequency are high.…”
Section: Event 1: March 19 2020mentioning
confidence: 99%
“…The condition for this resonance is satisfied if protons move along the field in the opposite direction to the waves. Interaction with EMIC waves is also believed to be an important loss mechanism for ∼ hundreds keV-several MeV radiation belt electrons, which can undergo cyclotron resonance with EMIC waves and consequent pitch-angle scattering into the atmosphere through the anomalous Doppler-shifted cyclotron resonance (Horne and Thorne, 1998;Summers et al, 2007;Blum et al, 2015;Capannolo et al, 2021). Since EMIC waves are predominantly left-hand polarized, electrons must overtake the wave with a velocity sufficient to Doppler shift the wave frequency to the relativistic electron cyclotron, frequency reversing the relevant sense of polarization from left-to right-handed.…”
Section: Introductionmentioning
confidence: 99%